Estudo das propriedades ópticas dos aerossóis no norte da África e da influência da zona de convergência intertropical no transporte de poeira mineral em direção a América do Sul - Veiga, Adilson Vladmir Cabral da [UNIFESP] (2017)
Abstract Every year a large amount of mineral dust is emitted from the Sahara desert, which is mostly transported over the tropical Atlantic Ocean. During the boreal summer, transport mainly takes place towards the south of North America and Caribbean, while the north of South America is the main receiver of the saharan dust in the winter. Although there has been a significant improvement in the understanding of the transport over the tropical Atlantic, there are still many unclear aspects, especially when transport takes place towards South America. One of the factors of uncertainty is a probable interaction between the dust plume and the Intertropical Convergence Zone (ITCZ) during the transport. In order to contribute to the understanding of this issue, firstly, the spatial and temporal variability of aerosols and water vapor across the dust source region (North Africa) was characterized and analyzed using ground-based remote sensing data. Afterwards, it was analyzed possible relations between the position and the intensity of the ITCZ and the aerosol plume across the tropical Atlantic using satellite remote sensing data between the years 2000 and 2015. As indicators of dust plumes, the aerosol optical depth (AOD) and the Ångström exponent (AE) were used, while the columnar precipitable water content (PWV) and the out-going longwave radiation (OLR) at the top of the atmosphere were used as indicators of the ITCZ.The analyzed experimental sites located in North Africa showed that the aerosol scenario is dominated by mineral dust almost all year round, although seasonal features are quite variable. However, in the southernmost sites in the Sahel region, the influence of biomass burning aerosols is important, especially in the end of the year. Across the tropical Atlantic, both the ITCZ and the Saharan plume showed strong seasonality, reaching their northernmost position during the boreal summer. Studies were carried out by contrasting ITCZ position interannual variability with the variation of the dust plume core position across the tropical Atlantic . Even in extreme cases of position variation, we were not able to identify a systematic relationship between the position of the core of the two climatic elements. However, with regard to the intensity, it was observed that stronger ITCZ was associated with the occurrence of a weaker plume, while weaker ITCZ was found associated with stronger dust plume. This behavior may be a consequence of both a decrease in the emission of mineral dust due to an increase of soil moisture in periods of intense ITCZ, and an increase of wet removal of aerosols during transport over Atlantic.